Study of the effect of hull geometry on the towing resistance of motor ferries when overcoming water obstacles - A. V. Mesropyan; R. R. Rakhmatullin (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The article studies the influence of the hull geometry on the towing resistance and speed of ferry vehicles on the water when overcoming water obstacles.Methods. 3D modeling methods are used in CAD and CAE packages to study the degree of influence of the hull geometry on the water resistance to the movement of the ferry vehicle, which makes it possible to accurately model the working processes occurring when flowing around motor ferries.Results. The analysis of the results of computer simulation of the movement of a ferry vehicle of the original design on the water is carried out. The advantages and disadvantages of the ferry bridge machine of the original design are determined, and various variants of design and layout schemes are proposed, the use of which allows increasing the speed and maneuvering characteristics of ferry vehicles.Conclusion. A variant of the design and layout scheme of a motor ferry is proposed, which allows improving the hydrodynamic characteristics of the ferry vehicle body by using modern technical solutions aimed at reducing towing resistance and increasing the speed of transportation when overcoming water obstacles.